Enhancing the criminology of mobility: A need for interdisciplinary and multi-sited research approaches. Introduction: Wzmacniając kryminologię mobilności. O konieczności interdyscyplinarnych i wielostanowiskowych badań i podejść. Wprowadzenie (Archives of Criminology, 2024)
Scholars from various disciplines, geographic locations and research traditions have examined border dynamics – investigating what occurs at borders, how it happens, its origins, consequences and normative implications. This has given rise to the burgeoning field of the “Criminology of Mobility”, an academic discipline focussed on issues such as citizenship, race, gender, ethnicity and immigration control. This relatively new and innovative academic discipline delves into the processes of inclusion and exclusion both at and within state borders, often employing methods traditionally associated with the criminal justice system, law enforcement and military operations – frequently without the safeguards typically in place. Scholars in this field investigate how existing inequalities – particularly those related to gender, race, nationality and class – are exacerbated by new power structures and systems of belonging. We have observed that there remains a notable lack of diversity in research from global regions, as well as a lack of attention to the perspectives of those directly affected by or involved in border control mechanisms and their extraterritorial dimensions. This special issue is a step to address this gap.